The Religiosity of American College and University Professors. - Gross, Neil; Simmons, Solon (Sociology of Religion)
For more than a century most U.S. colleges and universities have functioned as secular institutions. But how religious are American college and university faculty in their personal lives? We answer this question by analyzing data from a new, nationally representative survey of the American professoriate. Contrary to the view that religious skepticism predominates in the academy, we find that the majority of professors, even at elite research institutions, are religious believers. We go on to examine the distribution of faculty religiosity across institutions, fields, and other variables, and identify a number of issues that future research—sensitive to the fact that religious faith and academic life, at least in the American context, are by no means mutually exclusive—should take up. Reprinted by permission of the publisher.